Transcending recreational functionality: Adult EFL learners’ views on song-assisted language learning from an andragogical perspective - Ghidhaoui, Ranyme (Working Papers in Language Pedagogy, 2024)
Complementary to its entertainment value, music is known for having educational relevance in foreign language learning, a topic which is often overlooked in andragogical studies. The present inquiry sought to explore the use of songs in language learning by focusing on the perceptions and experiences of adult EFL learners. The qualitative research data are drawn from semi-structured interviews conducted with 15 adult EFL learners of different occupational and cultural backgrounds. The study findings reveal that music is omnipresent in adult EFL learners’ lives, both as a means of entertainment or ‘alternative therapy’ and as an opportunity for promoting language learning. The interviewees emphasized the way that songs enhance their learning experience by developing their reading comprehension and speaking skills. However, more emphatically, they reinforced the role of songs in facilitating vocabulary learning, namely the enrichment of their lexical repertoire. While the collected data suggest a consensus concerning the positive effects of songs, some participants argued that any learning gain is conditioned by several classroom-related factors. Future research can benefit from a discussion on the practical applications of songs in the adult EFL classroom.